Experimental and mechanical model for predicting the behaviour of minor axis beam-to-column semi-rigid joints - Lima, L. R. O. de (2002)
This paper describes a series of experimental tests followed by finite element simulations produced to enable the prediction of moment resistance and rotation capacity of minor axis beam-to-column semi-rigid connections. These investigations motivated the development of a mechanical model to assess the connection's structural response. The mechanical model is based on the component method of design, in accordance with the Eurocode 3 specification. This philosophy implies that each joint component is represented by a spring possessing a non-linear force versus displacement (F-[Delta]) curve. The model was subsequently calibrated against experimental and finite element results previously performed.